Pathological Fractures of the Mandible: Our Department’s 15-Year Experience - Georgios Chatziantoniou; Dimitris Tatsis; Solon Politis; Antonios Saramantos; Nikolaos Koukolis; Konstantinos Paraskevopoulos (Diagnostics)
Background/Objectives: Pathological fractures of the mandible are uncommon and often result from underlying conditions such as osteoradionecrosis, malignancies, or medication-related osteonecrosis of the jaw (MRONJ). Their management is challenging due to compromised bone quality and complex patient comorbidities. This study presents a 15-year experience from a tertiary oral and maxillofacial surgery center, highlighting the clinical characteristics, etiologies, treatment approaches, and outcomes of these fractures. Methods: A retrospective review was conducted on patients diagnosed with pathological mandibular fractures between 2010 and 2024. Data collected included demographics, fracture etiology and location, diagnostic imaging, treatment modality, complications, and long-term outcomes. Results: Fifty patients met the inclusion criteria. The mean age was 66.4 years, with a predominance of male patients (78%). The most common etiology was osteoradionecrosis (48%), followed by primary malignancy (22%) and MRONJ (16%). In 82% of cases, surgical management was required, most frequently involving marginal or segmental mandibular resection (gnathectomy), with or without immediate reconstruction. Conservative treatment was reserved for select cases with high surgical risk. Complications occurred in 54% of patients, including persistent fistulas, pathological communication with the skin or oral cavity, and the need for revision surgery. Long-term follow-up revealed variable survival, with many patients experiencing reduced quality of life due to complex postoperative courses. Conclusions: Pathological fractures of the mandible present significant diagnostic and therapeutic challenges, particularly in patients with osteoradionecrosis or malignancies. Early diagnosis and individualized, multidisciplinary treatment planning are essential. This study underscores the need for a standardized classification system and treatment algorithm to guide management and improve outcomes in this complex patient population.